The role of administrative leadership in dealing with work stress: An empirical study on employees in governance in Riyadh region - Al-Othman, Abdullah bin Abdul Rahman (Journal of Economic, Administrative and Legal Sciences, 2018)
The problem of the study is to identify the role of administrative leadership in dealing with the pressures of work through the perspective of employees، And sources of work pressure for individuals working in organizations. Also Provide suggestions and recommendations for future studies on the role of administrative leadership in dealing with work pressures. This research aims to identify the role of administrative leadership in dealing with the pressures of work through the perspective of employees. As well as identify sources of work stress for individuals working in organizations. The importance of the study through the contribution of the results of this study to support the current and future plans and policies for the development of performance of employees in government agencies of the state. To achieve this، a special questionnaire designed on the Likert scale was prepared and distributed to the sample، The field approach methodology was used as well as the "desktop method together. One of the findings of the researcher that there is a trend towards approving the availability of positive organizational climate and the role of administrative leadership in dealing with the pressures of work.One of the most important recommendations is the need to provide an encouraging work environment for the employee in order to increase efficiency and increase the effort of the employee and intensify training programs on how to deal with the pressures of work for employees.
Keywords: administrative leadership; government agencies; administrative employee